Effect of spraying with different concentration of zinc and iron on seedling growth of sour orange (Citrus aurantium L.). - Abeed, Mohammed H.; AL-Rubaei, Suzan M.K.; Hasan, Manar A.F.; Mahmood, Ola H. (Journal of Kerbala for Agricultural Sciences, 2018)
An experiment was conducted in lath house at the college of Agriculture, Karbala university during the growth season of 2017 to study the effect of different concentration of zinc and iron on seedling growth of sour orange ,Three replicates were used for each treatment .Zinc was used at three level 0,50 and100 mg.L-1 and three level of Iron 0,25 and 50 mg.L-1 .the seedling were sprayed at two interval 15/3/2017 and 30/3/2017 and they were irrigated one day before spraying dates .the experiment was conducted according to the completely Randomized Design(C.R.D)and analysis of variance (ANOVA)was based on L.S.D 0.05 .All measurements were taken at the end of June, the results showed as follow 1-The concentration of Zinc at 100 mg.L-1 significantly surpassed all other concentration regarding all studied characters height of seedling, stem diameter ,number of leaves, leaf area, dry weight of shoot system ,root length ,root volume, root diameter, dry weight of root system ,chlorophyll content in leaves ,Nitrogen percentage in leaves ,protein percentage in leaves ,Zinc concentration in leaves and Iron concentration in leaves. Which gave 58.11 cm,8.39 mm,83.11 leaf.seedling-1, 3250cm2, 14.51g, 36.00cm, 29.33cm3, 3.20cm, 8.14g, 51.52mg.100g-1 fresh weight, 3.55%, 22.17%, 48.91mg.L-1 and 64.50 mg.L-1 respectively. 2-Iron concentration at 50 mg.L-1 significantly surpassed all other concentration regarding all studied growth characters which gave55.00 cm ,7.65 mm ,73.89 leaf.seedling-1 , 2553 cm2 ,12.48 g.seedling-1, 31.44 cm, 24.89 cm3 , 3.12 cm ,6.98g.seedling-1, 49.13mg.100g-1 fresh weight , 3.35% , 20.90%, 47.43 mg.L-1 and 62.11 mg.L-1 respectively 3-The interaction between Zinc and Iron had no significant effect on the most character of growth including (stem diameter)number of leaves ,leaf area, dry weight of shoot system, root length, root volume ,root diameter ,chlorophyll content in leaves ,Nitrogen percentage ,protein percentage, Zinc concentration in leaves and Iron concentration in leaves however the significant effect of this interaction was on height of seedling and dry weight of root system at the concentration of 100 mg.L-1 of Zinc and 50 mg.L-1 of Iron gave 64.67 cm and 9.27g respectively.